Plaque Size Heterogeneity: a Genetic Trait of Lymphocytic Choriomeningitis Virus - Pulkkinen, A. J. (1970)
All of the ten strains of lymphocytic choriomeningitis virus assayed on BHK 21/13S cells showed various degrees of plaque size heterogeneity. The amount of virus released from these plaques was usually very small because of rapid photodynamic inactivation by neutral red. When virus from large and small plaques of a specific strain was plated, the same distribution of plaque size was obtained from each clone. Although it was shown that surface virus could possibly be randomly distributed at the time of addition of neutral red overlays, no virus could be isolated from nonplaque areas. Two different strains of virus (CA1371 and WE) with markedly different plaque size ranges were separated by plaque excision from plates infected with a mixture of both viruses.